2005
DOI: 10.1007/s00261-005-0346-0
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant infection with emphysematous changes in the biliary tract and air-filled liver abscesses

Abstract: Gas-producing infections are related to anaerobic bacteria and usually associated with immunosuppressive pathologies such as diabetes and have a fulminating course. We present the clinical course of a patient with diabetes whose infection progressed rapidly and ended in her dramatic death in a short period; surgical therapy was impossible, and the disease behaved similarly to type I emphysematous pyelonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Many previous cases and our case revealed that diabetes mellitus seemed to be a major risk factor for EH. [1,3,4,8,10,11] Gas collection in the lesion mainly comes from the mixed acid fermentation of glucose, including nitrogen, hydrogen, carbon dioxide, and oxygen. [12] Patients with diabetes have elevated blood glucose levels, and associated microangiopathy impairs the transportation of gas.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous cases and our case revealed that diabetes mellitus seemed to be a major risk factor for EH. [1,3,4,8,10,11] Gas collection in the lesion mainly comes from the mixed acid fermentation of glucose, including nitrogen, hydrogen, carbon dioxide, and oxygen. [12] Patients with diabetes have elevated blood glucose levels, and associated microangiopathy impairs the transportation of gas.…”
Section: Discussionmentioning
confidence: 99%
“…The histologic feature of emphysematous hepatitis was briefly described in a postmortem liver specimen obtained by autopsy [ 4 ]. The authors described clearly defined empty spaces covered by a patch of leukocytes without other associated changes.…”
Section: Resultsmentioning
confidence: 99%
“…Key information about the articles was extracted into a predefined datasheet: study characteristics include author, year of publication, patient characteristics (age and comorbidities), laboratory values (PCT levels, WBC levels, CRP levels, AST/ALT, bilirubin), method of diagnosis and imaging results, microbiological documentation (blood culture and/or culture from a liver sample), patient’s management and outcome. We identified 14 cases in the literature ( Table 1 ) [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are currently no treatment guidelines for this fulminant condition as adequate surgical debridement is generally unobtainable and attempts at percutaneous drainage and antibiotics have not been reported to be effective. 23,24 Emphysematous pancreatitis is a rare and life-threatening condition associated with acute pancreatitis. Plain radiography typically shows nonspecific findings, such as scattered gas in the mid abdomen.…”
Section: Intraparenchymal Airmentioning
confidence: 99%